Observations of interplanetary scintillation of the 2005 May 13 coronal mass ejection: numerical models. Issue 1 (22nd September 2021) - Chang, O; González, R F; Bisi, M M; Fallows, R A
ABSTRACT: The 2005 May 13 eruption was an Earth-directed coronal mass ejection (CME) observed using the Multi-Element Radio-Linked Interferometer Network telescope system in the UK as it traversed the Interplanetary Medium on 2005 May 14. Observations of interplanetary scintillation (IPS) provide information on the solar wind conditions, which include velocities and density. In addition, it is also possible to calculate other parameters related to the turbulence and geometry of density irregularities in the solar wind from observations of IPS. Previous analyses have shown that IPS information can be difficult to interpret when a complex structure is crossing the line of sight since the physical properties of the plasma may change quite drastically with distance from the Sun. In order to compare and relate the internal structure of a CME and its physical changes, with the results from observations of IPS obtained previously, we carried out a numerical simulation of the 2005 May 13 eruptive event as it propagates into the IPM, adapting the geometrical properties derived by IPS analysis. In this work, we give a possible explanation of some signatures of CME sub-structure from the point of view of the IPS technique combined with what the modelling reveals.